Beyond Andromeda: Improving Therapy for Light Chain Amyloidosis - Kaufman, Gregory P.; Cerchione, Claudio (Frontiers in Oncology, 2021)
Therapy for light chain amyloidosis (AL) continues to evolve and a new standard of care for the disease is rapidly forming. The risk of early death however, mainly from cardiac complications, remains an important benchmark yet to be definitively improved upon. This brief review explores recent advances in plasma cell directed therapy for AL, highlighting unique factors specific to these patients and AL biology driving differences in treatment strategies and clinical development compared with multiple myeloma. Improving upon proteasome inhibitor based upfront therapy combinations with the addition of anti-cd38 antibodies has shown promise with improved response rates in the ANDROMEDA (NCT03201965) study. Though depth and kinetics of achieving deep hematologic response as well as rates of biomarker defined organ response were improved with the addition of daratumumab to the combination of bortezomib, cyclophosphamide, and dexamethasone, death rates in each arm remained similar. Evaluation of other targeted and novel therapies in AL is ongoing and we highlight efforts evaluating BCMA directed therapy, BCL-2 family inhibitors, and other novel agents in the field. We also look ahead to efforts to reimagine the clinical development of anti-fibrillar therapies after late phase study failures. Upcoming anti-amyloid fibril antibody studies explore opportunities to improve outcomes for the sickest AL patients with advanced cardiac disease, focusing on improving overall patient survival and reducing the risk of early death in this uniquely frail population.